Anticancer properties of ester derivatives of betulin in human metastatic melanoma cells (Me-45). Issue 1 (December 2017) - Drąg-Zalesińska, Małgorzata; Drąg, Marcin; Poręba, Marcin; Borska, Sylwia; Kulbacka, Julita; Saczko, Jolanta
Abstract Background Betulinic acid and betulin are triterpenes that have anticancer properties in various types of cancer. Unfortunately, the bioavailability and the bio-distribution of betulinic acid and its metabolic precursor, betulin are very low because of poor solubility in aqueous buffers. Methods In this study, we examined the anticancer properties of the ester derivatives of betulin compared to their precursors in a malignant melanoma cell line. We assessed five amino acid esters of betulin. The compounds contained four basic amino acids—natural lysine (l -Lys-OH) and three of its derivatives (l -Dap-OH, l -Dab-OH, andl -Orn-OH)—and alanine (l -Ala-OH) as a negative control (amino acid without an amine group in the side chain). The derivatives were more soluble than their precursors (betulin and betulinic acid) in water. The betulin esters were tested in the malignant melanoma cell line Me-45. To evaluate the cytotoxicity, MTT test was performed after 24, 48 and 72 h of incubation with the test compounds at a concentration range of 0.75–100 μM. For analysis of the apoptotic activity, TUNEL assay was performed. Additionally, expression of caspase-3 and PARP-1 was investigated immunocytochemically. Results The highest biological activity was observed with the lysine ester. The results showed that the highest cytotoxicity and the highest number of positively stained nuclei in metastatic melanoma Me-45 cells were obtained after 72 h of incubation with betulin derivatives containing lysine and ornithine. Conclusions The betulin ester derivatives showed enhanced antitumor activity compared to their non-modified precursors. Esters of betulin can be more potent anticancer agents than their precursor as a consequence of the rapid bioavailability and increased concentration in cancer cells.